The Cds.71 on TMS5 May Act as a Mutation Hotspot to Originate a TGMS Trait in Indica Rice Cultivars - Tan, Yanning; Sun, Xuewu; Fang, Baohua; Sheng, Xiabing; Li, Zheli; Sun, Zhizhong; Yu, Dong; Liu, Hai; Liu, Ling; Duan, Meijuan; Yuan, Dingyang (Frontiers in Plant Science, 2020)
The gene tms5, which controls thermo-sensitive genic male sterility (TGMS), has been widely used in two-line hybrid rice breeding in China. The tms5 lines have two sources, namely, AnnongS-1 (AnS) and Zhu1S (ZhS) and, interestingly, are commonly subject to an alteration at cds.71. However, whether cds.71 acts as a mutation hotspot is unknown. Herein, another tms5 mutant named T98S (induced from T98B by irradiation) was used to explore this. First, the gene of tms(t) responsible for T98S was fine-mapped on chromosome 2 based on an F2 group of T98S/R893. In T98S, the candidate gene TMS5 (LOC_Os02g12290.1) mutated at cds.71 with a transversion from cytosine (C) to adenine (A), as also observed in AnS and ZhS. Moreover, the entire coding sequence of TMS5 from T98B converted T98S from sterile to fertile by Agrobacterium tumefaciens-mediated transformation, confirming that T98S is controlled by tms5. Next, detection on nearly 40,000 single nucleotide polymorphisms (SNPs) on Rice 56K SNP Array revealed T98S was 99.99% similar to T98B but only 72.84% and 77.47% similar to AnS and ZhS, respectively, demonstrating that T98S originated from T98B rather than from existing tms5 lines. Furthermore, the cds.70 was found to exist as a T/G haplotype, and it was T rather than G that helped to induce a TGMS trait. The T frequency was 67.52% in indica rice but decreased to 1.75% in japonica rice in 2,644 cultivars tested, which partly explains why tms5 mutants were mostly found in indica lines. Our findings provide evidence that cds.71 may act as a mutation hotspot and clues for breeding TGMS lines in a more efficient way.